2010
DOI: 10.1523/jneurosci.0477-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Binding Vascular Endothelial Growth Factor (VEGF) Isoforms Guide Granule Cell Migration in the Cerebellum via VEGF Receptor Flk1

Abstract: Vascular endothelial growth factor (VEGF) regulates angiogenesis, but also has important, yet poorly characterized roles in neuronal wiring. Using several genetic and in vitro approaches, we discovered a novel role for VEGF in the control of cerebellar granule cell (GC) migration from the external granule cell layer (EGL) toward the Purkinje cell layer (PCL). GCs express the VEGF receptor Flk1, and are chemoattracted by VEGF, whose levels are higher in the PCL than EGL. Lowering VEGF levels in mice in vivo or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 79 publications
3
91
0
Order By: Relevance
“…) (data not shown). In agreement with our data, it has been previously demonstrated that VEGF in the cortex and cerebellum is expressed by cortical neurons and Purkinje cells, respectively (Ogunshola et al, 2002;Ruiz de Almodovar et al, 2010). This differential expression pattern of VEGF may explain the different effects of conditioning medium derived from cultures of astrocytes from P3 SVZ, cortex, cerebellum, and adult SVZ on BV development and growth (Fig.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…) (data not shown). In agreement with our data, it has been previously demonstrated that VEGF in the cortex and cerebellum is expressed by cortical neurons and Purkinje cells, respectively (Ogunshola et al, 2002;Ruiz de Almodovar et al, 2010). This differential expression pattern of VEGF may explain the different effects of conditioning medium derived from cultures of astrocytes from P3 SVZ, cortex, cerebellum, and adult SVZ on BV development and growth (Fig.…”
supporting
confidence: 92%
“…Recently, it has been demonstrated also that Purkinje cell-derived VEGF guides granule cell migration in the cerebellum (Ruiz de Almodovar et al, 2010). However, the role of VEGF in neuroblast migration in the adult RMS remains controversial (Wittko et al, 2009;Licht et al, 2010).…”
Section: Development Of the Postnatal Migratory Streammentioning
confidence: 99%
“…They stimulate neurogenesis, long-term potentiation, and learning, whereas low VEGF levels cause or aggravate motoneuron degeneration, and VEGF delivery delays paralysis in preclinical models (1). During cerebellar development, VEGF chemoattracts granule cells (GCs) from the external GC layer (EGL) toward the internal GC layer (IGL) (2). This chemotactic activity of VEGF for GCs in vivo is mediated by direct activation of Flk1 in GCs, independently of its angiogenic activity (2).…”
mentioning
confidence: 99%
“…During cerebellar development, VEGF chemoattracts granule cells (GCs) from the external GC layer (EGL) toward the internal GC layer (IGL) (2). This chemotactic activity of VEGF for GCs in vivo is mediated by direct activation of Flk1 in GCs, independently of its angiogenic activity (2). However, the mechanisms via which VEGF regulates GC migration in the cerebellum remain unknown.…”
mentioning
confidence: 99%
“…In the neonatal cerebellum, the granule cells migrate radially from the external granular layer (EGL), which expresses low levels of VEGF-A toward the Purkinje cell layer (PCL), where high levels of matrix-bound VEGF-A isoforms are deposited around the dendrites of Purkinje cells. Granule-cell-specific Vegfr-2 knockout mice provided in vivo evidence for a direct chemo-attractive effect of VEGF on neurons via VEGFR-2 signaling (Ruiz de Almodovar et al 2010).…”
Section: Vegf Signaling In Neuronal Progenitors During Development Anmentioning
confidence: 99%